Exploring the Reasons for Marital Dissolution Among Residents in Hosanna, Southwest Ethiopia: A Phenomenological Study - Asfaw, Likawunt Samuel; Alene, Getu Degu (CV. Literasi Indonesia, 2023)
Marital dissolution is a major social determinant of health, with enormous and ultimately irreversible consequences for children, the individuals involved, and society as a whole. This study explored the reasons for marital dissolution in Hosanna, Ethiopia. A phenomenological study was carried out on 29 individuals selected based on their lived experiences of marital breakdown using the maximum variation purposive sampling technique. We used this method to capture a wide range of experiences related to marital dissolution. We delineated a thematic analysis to drive the initial codes directly from the text data. Open Code 4.02 was used to process data. Five themes emerged as drivers of marital breakdown, including socioeconomic reasons, communication and commitment issues, external pressures, attitude and behavioral changes, and disagreements on sexual matters and personal interests. Likewise, four themes emerged to advance the prevention measures of marital dissolution, including 1) commitment to the relationship, 2) improving knowledge and skills in marital relationships, 3) protecting marriages from external stressors, and 4) improving appearance and well-being. Behavioral changes in marital relationships are one of the causes of marital breakdown. This study implies the need for interventions designed and built in the local context to mitigate the drivers of marital dissolution.